Epistemología y metodología configuracional en las ciencias humanas y sociales (2018)
This article proposes an epistemology that treats the theory as a constant process of scientific knowledge and intelligibility of the real configuration, giving priority in that process the active participation and leading the study subjects and researchers, from the identification of configurations that characterized the human and social processes studied. It reflects on the configurational logic of scientific knowledge and presents a methodological procedure for scientific argumentation and understanding in social and human sciences. Explains the relationship between macro, meso and micro-configurations. © 2018, Universidad del Zulia. All rights reserved.